Amalan Pengangkatan Kanak-Kanak di Malaysia: Satu Analisis Perbandingan (Jurnal Pembangunan Sosial, 2018)
Taking a child for adoption has been a common practice in mankind since Jahiliah era. For instance, the Prophet Muhammad SAW had adopted a child known as Zaid Harithah. However, the revelation of the Surah al Ahzab (4-5) of the Holy Quran had corrected the practice and leading to different understanding of the adoption concept between the Moslem and Non-Moslem communities. Today, the practice of adoption is noticeable in varied forms and understandings in Malaysia. Hence, this article explains the adoption practices in Malaysia especially the concepts of adopted child, breastfed child, and foster child between the Moslem and Non-Moslem communities. Library research method was used to conduct the comparison. The three concepts have distinct meanings in the local context and have been affecting the norm, cultural practices and legislation in Malaysia. Thus, it is suggested that educating general public to accurately comprehend the concept of adoption in Malaysia is needed. This is to avoid unnecessary confusion and difficulties in practicing the placement.